Impact of changing treatment strategy based on circulating tumor cells on postoperative survival of breast cancer - Wang, Zihan; Xu, Wei; Yang, Yanlian; Gao, Guoxuan; Teng, Changsheng; Ge, Zhicheng; Zhang, Huiming; Yuan, Zhu; Ding, Guoqian; Wang, Yang; Li, Peixin; Xu, Yaqian; et al. (Frontiers in Oncology, 2022)
Background: We sought to explore the impact of changing treatment strategy based on circulating tumor cells (CTC) on postoperative survival of breast cancer. Methods: We retrospectively analyzed records of patients who underwent surgery for early-stage breast cancer at Beijing Friendship Hospital from January 2016 to January 2018 and regularly underwent CTC examination after surgery. During the regular examination and CTC monitoring, the patients with positive CTC results and without distant metastasis had their treatment regimen changed. Results: Of 109 patients who received CTC examination regularly after surgery, 61 (56.0%) were CTC-positive during postoperative follow-up, including 33 ER or PR-positive, and 28 ER and PR-negative patients. Of the 33 ER or PR-positive patients, 20 changed endocrine therapy drugs. Compared with those without replacement, those with changed endocrine therapy strategy had higher CTC clearance rates (90.0% vs. 53.8%, p=0.04) and significantly lower CTC-positive values (1.70 ± 1.72 vs. 0.62 ± 0.65, p = 0.04). Among the 28 patients who were CTC positive and ER and PR-negative, 11 used capecitabine. Compared with non-users, the capecitabine users had higher CTC clearance rates (100.0% vs. 52.9%, p=0.01) and more significant decrease in CTC-positive values (2.09 ± 1.14 vs. 0.82 ± 1.67, p=0.04). Disease-free survival (DFS) at 1, 3, and 5 years was significantly longer in those who changed treatment than in those who did not (respectively, 96.6% vs. 89.6%, 92.8% vs. 56.9%, 69.0% vs. 47.8%, p<0.01). By changing the treatment strategy, CTC-positive patients achieved DFS that was not significantly different from CTC-negative patients (95.0% vs. 97.7%, 77.5% vs. 82.9%, 57.6% vs. 59.9%, p=0.20). Conclusion: Timely change of treatment strategy for breast cancer patients with positive CTC results after surgery may improve CTC clearance rate and DFS.